Owner Ethnicity: The Determinant of Relationship between Environment Uncertainty and Performance - Andriany, Lussia Mariesti (Universitas Negeri Malang, 2017)
The aim of this research is to reveal effect of environment uncertainty which seen through competition level and costumer to performance. This research reveals the difference of relationship in environment uncertainty to performance between Chinese and non-Chinese business. Data are collected through direct survey to traditional retail owners by questionnaire and interview. Then, those data analyze in two stages, confirmatory factor analysis and simple regression with dummy variable. This research finds that there is no effect from environment uncertainty to performance. Also, there is no difference between Chinese and non-Chinese business in environment uncertainty to performance relationship.Â Keywords: ethnic of business ownership, environment uncertainty, performance